A global synthesis reveals biodiversity-mediated benefits for crop production - Dainese, Matteo; Martin, Emily A.; Aizen, Marcelo Adrian; Albrecht, Matthias; Bartomeus, Ignasi; Bommarco, Riccardo; Carvalheiro, Luisa G.; Chaplin-Kramer, Rebecca; Gagic, Vesna; Garibaldi, Lucas Alejandro; Cavigliasso, Pablo; Steffan-Dewenter, Ingolf (American Association for the Advancement of Science, 2021)
Human land use threatens global biodiversity and compromises multiple ecosystem functions critical to food production. Whether crop yield–related ecosystem services can be maintained by a few dominant species or rely on high richness remains unclear. Using a global database from 89 studies (with 1475 locations), we partition the relative importance of species richness, abundance, and dominance for pollination; biological pest control; and final yields in the context of ongoing land-use change. Pollinator and enemy richness directly supported ecosystem services in addition to and independent of abundance and dominance. Up to 50% of the negative effects of landscape simplification on ecosystem services was due to richness losses of service-providing organisms, with negative consequences for crop yields. Maintaining the biodiversity of ecosystem service providers is therefore vital to sustain the flow of key agroecosystem benefits to society.